Heat and Hypoxic Acclimation Increase Monocyte Heat Shock Protein 72 but Do Not Attenuate Inflammation following Hypoxic Exercise - Lee, Ben J.; Thake, Charles D. (Frontiers in Physiology, 2017)
Acclimation to heat or hypoxic stress activates the heat shock response and accumulation of cytoprotective heat shock proteins (HSPs). By inhibiting the NF-κB pathway HSP72 can preserve epithelial function and reduce systemic inflammation. The aim of this study was to determine the time course of mHSP72 accumulation during acclimation, and to assess intestinal barrier damage and systemic inflammation following hypoxic exercise. Three groups completed 10 x 60-minute acclimation sessions (50% normoxic VO2peak) in control (n = 7; 18°C, 35% RH), hypoxic (n = 7; FiO2 = 0.14, 18°C, 35% RH), or hot (n = 7; 40°C, 25% RH) conditions. Tumour necrosis factor-α (TNF-α), interleukin 6 (IL-6), interleukin 10 (IL-10), and intestinal fatty acid binding protein (I-FABP) were determined at rest and following a cycling normoxic stress test (NST; 2 weeks before acclimation), pre-acclimation hypoxic stress test (HST1; FiO2 = 0.14, both at 50% normoxic VO2peak; 1 week before acclimation) and post-acclimation HST (48 hours; HST2). Monocyte HSP72 (mHSP72) was determined before and after exercise on day 1, 3, 5, 6, and 10 of acclimation. Accumulation of basal mHSP72 was evident from day 5 (p < 0.05) of heat acclimation and increased further on day 6 (p < 0.01), and day 10 (p < 0.01). In contrast, basal mHSP72 was elevated on the final day of hypoxic acclimation (p < 0.05). Following the NST, plasma TNF-α (-0.11 ± 0.27 ng.mL-1), IL-6 (+0.62 ± 0.67 ng.mL-1) IL-10 (+1.09 ± 9.06 ng.mL-1) and I-FABP (+37.6 ± 112.8 pg.mL-1) exhibited minimal change. After HST1, IL-6 (+3.87 ± 2.56 ng.mL-1), IL-10 (+26.15 ± 26.06 ng.mL-1) and I-FABP (+183.7 ± 182.1 pg.mL-1) were elevated (p < 0.01), whereas TNF-α was unaltered (+0.08 ± 1.27; p > 0.05). A similar trend was observed after HST2, with IL-6 (+3.09 ± 1.30 ng.mL-1), IL-10 (+23.22 ± 21.67 ng.mL-1) and I-FABP (+145.9 ±123.2 pg.mL-1) increased from rest. Heat acclimation induces mHSP72 accumulation earlier and at a greater magnitude compared to matched work hypoxic acclimation, however neither acclimation regime attenuated the systemic cytokine response or intestinal damage following acute exercise in hypoxia.